Giving Australian First-in-Family Students a Kick Start to University. - Chapin, Laurie A.; Oraison, Humberto; Nguyen, Thinh; Osmani, Sera; Keohane, Emily (Student Success v.14 n.1 p.60-70 https://doi.org/10.5204/ssj.2762, 2023)
Australian university students who are the first in their family to attend university are more likely to encounter challenges in their transition to university, and programs to support students are important for success and retention. Fifteen first-in-family (FiF) students participated in an Australian-first pilot orientation program. Program students had better engagement (attendance and study hours) and higher grades compared to a control group. There were no group differences in self-efficacy, program participants had steady social support over time while the control group experienced a decline across semester 1. Qualitative findings indicate that participants felt confident about their transition and did not report academic challenges. They had made connections and felt supported. Commute times were the most common adjustment reported. [Author abstract]